Dieta de Cyclura nubila nubila Gray, 1831 (Squamata: Iguanidae) en dos cayos del archipiélago de los Jardines de la Reina, Cuba - Marichal Arbona, Evelyn (Instituto de Ecología, A.C., 2016)
Cyclura nubila nubila is an endemic subspecies of Cuba and it has been listed as Vulnerable in the IUCN Red List. The present investigation was developed in November 2013 and February 2014 in Caguamas and Palomo cays, respectively. Thirty-seven fecal pellets were collected through fixed transects on sandy coast vegetation and subsequently moistened with water and alcohol to separate and identify diet‘s components. Nine species of plants in Caguamas and four in Palomo were identified as part of iguana‘s diet. The most frecuent plant species were Conocarpus erectus, Setaria parviflora and Thalassia testudinum in Palomo and Cochorus hirsutus in Caguamas. In Palomo 45% of fecal pellets contained corporal parts of dragonflies and 5% parts of crabs. The consumption of animal matter is due to the low floristic diversity of Palomo cay. The iguana‘s diet in Caguamas included more plant components mainly fruits. This study contributes to increase knowledge of trophic ecology and management of the species in the archipelago of Jardines de la Reina.